2013
DOI: 10.1111/ggi.12167
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of renin-angiotensin system components in acute stroke patients

Abstract: These findings suggest that changes of serum RAS components could reflect stroke subtypes and predict stroke severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…One recent study found that serum ACE2 levels within the first 24 hours post-stroke differ slightly by stroke subtype with lacunar exhibiting lower levels than cardioembolic strokes. 5 In rats, expression and activity of ACE2 in ischemic brain tissue is altered, 6 and we demonstrated that serum ACE2 activity is initially decreased, followed by rebound increases over the next several days. 4 Validating this decrease in human disease will provide further support for targeting ACE2 with neuroprotective interventions.…”
Section: Introductionmentioning
confidence: 71%
“…One recent study found that serum ACE2 levels within the first 24 hours post-stroke differ slightly by stroke subtype with lacunar exhibiting lower levels than cardioembolic strokes. 5 In rats, expression and activity of ACE2 in ischemic brain tissue is altered, 6 and we demonstrated that serum ACE2 activity is initially decreased, followed by rebound increases over the next several days. 4 Validating this decrease in human disease will provide further support for targeting ACE2 with neuroprotective interventions.…”
Section: Introductionmentioning
confidence: 71%
“…Higher levels of ACE2 were found among patients who experienced cardioembolic stroke versus other stroke subtypes 18 , although baseline or control ACE2 levels were not assessed for comparison. It has also been shown that ACE2 gene polymorphisms may be associated with increased risk for stroke 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it remains unknown whether circulating ACE2 levels have any relationship with ACE2 abundance in the respiratory system or intestinal tissues. Moreover, circulating ACE2 levels are increased in patients with cardiovascular diseases (CVDs), including heart failure [ 66 , 67 ] and arterial fibrillation [ 68 ], chronic kidney disease (CKD) [ 69 ], atherosclerosis [ 70 ], and stroke [ 71 ]. In addition, circulating ACE2 levels are reported to be higher in male than in female patients with heart failure [ 72 ].…”
Section: Covid-19 and Ace2mentioning
confidence: 99%